Clean and Healthy Lifestyle Behavior (PHBS Program) for Children with Intellectual Disability - Purba, Natalina; Gusar, Martua Reynhat Sitanggang (Jurnal Pendidikan Usia Dini, 2020)
The achievement of children's quality of life is undoubtedly linked to the development of positive habits that will continue to be practiced in future lives. This can be done by developing awareness and behavior of a balanced clean and healthy lifestyle. The purpose of this study was to determine the increase in the PHBS ability of children. Various efforts have been made so that children with intellectual disabilities can maintain their cleanliness. The efforts made by the teacher are still not maximal so that the delivery of information about PHBS must be completed by another method, namely demonstration. This research was conducted at SDLB 127710 Pematangsiantar5 with an action research method that refers to the Kurt Lewin model. Data collection techniques used purposive sampling and data analysis with the Wilcoxon test. The results showed an increase in understanding of the PHBS of children with intellectual disabilities able to learn SDLB 127710 Pematangsiantar through the demonstration method. This is evidenced by the increase in the score, where the initial assessment was obtained (59%), while in the first cycle, the average score was good (69.9%). In short, the understanding of children with intellectual disabilities being able to learn about PHBS is increased by using the demonstration method. Keywords: Intellectual Disability Children, PHBS program, Demonstration methods References Agarwal, R. (2017). Importancia de la atención primaria de salud en la sociedad. International Journal of Health Sciences, 1(1), 5–9. Aiello, A. E., Coulborn, R. M., Perez, V., & Larson, E. L. (2008). Effect of hand hygiene on infectious disease risk in the community setting: A meta-analysis. American Journal of Public Health, 98(8), 1372–1381. https://doi.org/10.2105/AJPH.2007.124610 Arip, M. pdfo., & Emilyani, D. (2018). Strategy to improve knowledge, attitude, and skill toward clean and healthy life behaviour. International Journal of Social Sciences and Humanities, 2(3), 125–135. https://doi.org/10.29332/ijssh.v2n3.222 Basheer, A., Hugerat, M., Kortam, N., & Hofstein, A. (2017). The effectiveness of teachers’ use of demonstrations for enhancing students’ understanding of and attitudes to learning the oxidation-reduction concept. Eurasia Journal of Mathematics, Science and Technology Education, 13(3), 555–570. https://doi.org/10.12973/eurasia.2017.00632a Bloomfield, S. F., Aiello, A. E., Cookson, B., O’Boyle, C., & Larson, E. L. (2007). The effectiveness of hand hygiene procedures in reducing the risks of infections in home and community settings including handwashing and alcohol-based hand sanitizers. American Journal of Infection Control, 35(10 SUPPL. 1). https://doi.org/10.1016/j.ajic.2007.07.001 Cavanaugh, L. K. (n.d.). Intellectual Disabilities (D. L. Porretta (Ed.); 6 th). Human Kinetics. Chang, Y. J., Lee, M. Y., Chou, L. Der, Chen, S. F., & Chen, Y. C. (2011). A Mobile Wetness Detection System Enabling Teachers to Toilet Train Children with Intellectual Disabilities in a Public School Setting. Journal of Developmental and Physical Disabilities, 23(6), 527–533. https://doi.org/10.1007/s10882-011-9243-3 Cummings, S., Bridgman, T., & Brown, K. G. (2016). Unfreezing change as three steps: Rethinking Kurt Lewin’s legacy for change management. Human Relations, 69(1), 33–60. https://doi.org/10.1177/0018726715577707 Dirjen P2P Kemkes RI. (2019). Rencana Aksi Program Pencegahan Dan Pengendalian Penyakit 2015-2019 ( Revisi I - 2018 ). Rencana AKSI Program P2P 2015-2019, 2019, 86. Flanagan, D. P., Alfonso, V. C., & Hale, J. B. (2010). The Wechsler Intelligence Scale for Children - Fourth Edition in Neuropsychological Practice. Handbook of Pediatric Neuropsychology, January, 397–414. Giridharan, K., & Raju, R. (2017). Impact of Teaching Strategies: Demonstration and Lecture Strategies and Impact of Teacher Effect on Academic Achievement in Engineering Education. International Journal of Educational Sciences, 14(3), 174–186. https://doi.org/10.1080/09751122.2016.11890491 Hooman, N., Safaii, A., Valavi, E., & Amini-Alavijeh, Z. (2013). Toilet training in Iranian children: A cross-sectional study. Iranian Journal of Pediatrics, 23(2), 154–158. Hung, J.-W., Chang, Y.-J., & Han, W.-Y. (2016). Game technology to increase range of motion for adolescents with cerebral palsy: a feasibility study. International Journal on Disability and Human Development, 16(3). https://doi.org/10.1515/ijdhd-2016-0026 Kang, Y. S., & Chang, Y. J. (2019). Using a motion-controlled game to teach four elementary school children with intellectual disabilities to improve hand hygiene. Journal of Applied Research in Intellectual Disabilities, 32(4), 942–951. https://doi.org/10.1111/jar.12587 Kementerian, & Indonesia, R. (2011). Profil Kesehatan Indonesia. Kemenenterian Kesehatan RI. Kesehatan, K. (2011). PHBS di Sekolah. Kementerian Kesehatan Republik Indonesia. Ketut Sudiana, I., Adiputra, N., & Budi Adnyana, P. (2020). Integrative Health Thematic Strategy Increases Learning Outcomes and Students ’Clean and Healthy Living Behaviors. Journal of Physics: Conference Series, 1503(1). https://doi.org/10.1088/1742-6596/1503/1/012050 Koh, W. M., Bogich, T., Siegel, K., Jin, J., Chong, E. Y., Tan, C. Y., Chen, M. I. C., Horby, P., & Cook, A. R. (2016). The epidemiology of hand, foot and mouth disease in Asia: A systematic review and analysis. Pediatric Infectious Disease Journal, 35(10), e285–e300. https://doi.org/10.1097/INF.0000000000001242 Kroeger, K., & Sorensen, R. (2010). A parent training model for toilet training children with autism. Journal of Intellectual Disability Research, 54(6), 556–567. https://doi.org/10.1111/j.1365-2788.2010.01286.x Laporan Akuntabilitas Kinerja Kementerian Kesehatan tahun 2014. (n.d.). Lee, R. L. T., & Lee, P. H. (2014). To evaluate the effects of a simplified hand washing improvement program in schoolchildren with mild intellectual disability: A pilot study. Research in Developmental Disabilities, 35(11), 3014–3025. https://doi.org/10.1016/j.ridd.2014.07.016 Lee, R. L. T., Leung, C., Tong, W. K., Chen, H., & Lee, P. H. (2015). Comparative efficacy of a simplified handwashing program for improvement in hand hygiene and reduction of school absenteeism among children with intellectual disability. American Journal of Infection Control, 43(9), 907–912. https://doi.org/10.1016/j.ajic.2015.03.023 Levato, L. E., Aponte, C. A., Wilkins, J., Travis, R., Aiello, R., Zanibbi, K., Loring, W. A., Butter, E., Smith, T., & Mruzek, D. W. (2016). Use of urine alarms in toilet training children with intellectual and developmental disabilities: A review. Research in Developmental Disabilities, 53–54, 232–241. https://doi.org/10.1016/j.ridd.2016.02.007 Noah Ekeyi, D. (2013). Effect of Demonstration Method of Teaching on Students’ Achievement in Agricultural Science. World Journal of Education, 3(6), 1–7. https://doi.org/10.5430/wje.v3n6p1 Pedoman Umum Program Indonesia Sehat dengan Pendekatan Keluarga. (2015). Kementerian Kesehatan Republik Indonesia. Purba, N., Handini, M. C. H., & Yetti, E. (2018). Development of Media Vocabulary Cards to Improve the Speech Competence of Children with Intellectual Disabilities. 6. Puspita, W. A., Sulistyorini, M. P., & Wibowo, B. (2020). Learning Clean, Healthy and Safe Life Behavior in Inclusive Early Childhood Education. 454(Ecep 2019), 270–274. https://doi.org/10.2991/assehr.k.200808.053 Putri, R. M., Rosdiana, Y., & Nisa, A. C. (2019). Application of Clean and Healthy Living Behavior (PHBS) From The Household Knowledge and Attitude Study. Journal Of Nursing Practice, 3(1), 39–49. https://doi.org/10.30994/jnp.v3i1.64 Rosenberg, N. E., Schwartz, I. S., & Davis, C. A. (2010). Evaluating the utility of commercial videotapes for teaching hand washing to children with autism. Education and Treatment of Children, 33(3), 443–455. https://doi.org/10.1353/etc.0.0098 Ruan, F., Yang, T., Ma, H., Jin, Y., Song, S., Fontaine, R. E., & Zhu, B. P. (2011). Risk factors for hand, foot, and mouth disease and herpangina and the preventive effect of hand-washing. Pediatrics, 127(4). https://doi.org/10.1542/peds.2010-1497 Shen, K., Yang, Y., Wang, T., Zhao, D., Jiang, Y., Jin, R., Zheng, Y., Xu, B., Xie, Z., Lin, L., Shang, Y., Lu, X., Shu, S., Bai, Y., Deng, J., Lu, M., Ye, L., Wang, X., Wang, Y., & Gao, L. (2020). Diagnosis, treatment, and prevention of 2019 novel coronavirus infection in children: experts’ consensus statement. World Journal of Pediatrics, 16(3), 223–231. https://doi.org/10.1007/s12519-020-00343-7 Steenkamp, L., Williams, M., Ronaasen, J., Feeley, A., Truter, I., & Melariri, P. (2020). Handwashing knowledge and practices among caregivers of pre-school children in underprivileged areas of Nelson Mandela Bay. South African Journal of Clinical Nutrition, 0(0), 1–5. https://doi.org/10.1080/16070658.2020.1769336 van Nunen, K., Kaerts, N., Wyndaele, J. J., Vermandel, A., & van Hal, G. V. (2015). Parents’ views on toilet training (TT): A quantitative study to identify the beliefs and attitudes of parents concerning TT. Journal of Child Health Care, 19(2), 265–274. https://doi.org/10.1177/1367493513508232 Walpole, R. E. (1955). Pengantar Statistika. Gramedia.